1998
DOI: 10.1183/09031936.98.12030595
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte counts and macrophage phenotypes in induced sputum and bronchoalveolar lavage fluid from normal subjects

Abstract: Bronchoalveolar lavage (BAL) is a well-standardized method for retrieving cells and soluble material from the lung. An alternative, less invasive method to recover such material is induced sputum (IS). The method provides an opportunity to perform frequent observations, in order to follow a dynamic course of pulmonary inflammatory disease and effects of treatment. Recent research on IS has focused on markers of inflammation in asthma and the method has, in that context, proven to be reliable, for instance in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 19 publications
(29 reference statements)
3
18
1
2
Order By: Relevance
“…We found positive correlations between of the total counts of certain inflammatory cell populations; this was in agreement with the recent knowledge on the character of inflammation in ILD [5,[21][22][23]. Particularly, a common participation of neutrophils and eosinophils was observed in certain ILD types [1,3,21].…”
Section: Discussionsupporting
confidence: 92%
“…We found positive correlations between of the total counts of certain inflammatory cell populations; this was in agreement with the recent knowledge on the character of inflammation in ILD [5,[21][22][23]. Particularly, a common participation of neutrophils and eosinophils was observed in certain ILD types [1,3,21].…”
Section: Discussionsupporting
confidence: 92%
“…The data of control patients are in line with published normal ranges [28]. Patients with active sarcoidosis had higher cell counts than patients with inactive disease and controls.…”
Section: Bal Characteristicssupporting
confidence: 89%
“…The lack of correlation between IS and BAL cell differential counts has long been reported in healthy subjects 25 and in asthmatic patients. 26 Intra-individual comparison of IS and BAL in healthy subjects showed that IS samples contained a lower total cell count, a lower percentage of macrophages and a higher neutrophil proportion than BAL samples.…”
Section: Discussionmentioning
confidence: 98%